2013
DOI: 10.1002/phar.1334
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Metformin Dose on Cancer Risk Reduction in Patients with Type 2 Diabetes Mellitus: A 6-Year Follow-up Study

Abstract: The magnitude of cancer risk reduction and prolonged cancer onset times produced by metformin in patients with type 2 diabetes depended on the dose of metformin, regardless of whether metformin was used alone or combined with other antidiabetic drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…However, inflammation is an established component of carcinogenesis, and, since HF is characterized by chronic inflammation and neurohormonal activation, it may be speculated that chronic inflammation plays a role in the increased risk of development of cancer in HF. This is supported by growing evidence suggesting an increased risk of cancer among patients with other chronic diseases with an inflammatory component such as type 2 diabetes, where breast, colorectal, pancreatic, and oesophageal cancer have been suggested to be more frequent and to be associated with a poor prognosis . At the tissue level, an association between chronic inflammation and cancer has also been demonstrated for inflammatory bowel disease and colorectal cancer …”
Section: Discussionmentioning
confidence: 84%
“…However, inflammation is an established component of carcinogenesis, and, since HF is characterized by chronic inflammation and neurohormonal activation, it may be speculated that chronic inflammation plays a role in the increased risk of development of cancer in HF. This is supported by growing evidence suggesting an increased risk of cancer among patients with other chronic diseases with an inflammatory component such as type 2 diabetes, where breast, colorectal, pancreatic, and oesophageal cancer have been suggested to be more frequent and to be associated with a poor prognosis . At the tissue level, an association between chronic inflammation and cancer has also been demonstrated for inflammatory bowel disease and colorectal cancer …”
Section: Discussionmentioning
confidence: 84%
“…Population-based studies show that metformin, widely used for the treatment of type 2 diabetes mellitus, [8][9][10] is associated with a dose-dependent reduction in cancer risk. 21 Previous studies demonstrated that metformin restrained prostate cancer cell proliferation, migration, and invasion and enhanced apoptosis. 13,22 These findings are consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin has been demonstrated to exert anticancer effects in several types of cancer, including those affecting the liver, colon, breast, pancreas, and prostate ( 7 ). However, the utility of metformin in the prevention and treatment of bladder cancer has not been specifically investigated.…”
Section: Discussionmentioning
confidence: 99%
“…There has been considerable interest in the antitumor properties of metformin. Lin et al ( 7 ) reported that the magnitude of cancer risk reduction and prolonged cancer onset times produced by metformin in patients with type 2 diabetes depended on the dose of metformin. Therefore, we determined the potential association of a history of DM and glycemic control with tumor characteristics and recurrence-free survival (RFS) and progression-free survival (PFS) among patients who underwent transurethral resection (TUR) for NMIBC.…”
Section: Introductionmentioning
confidence: 99%